Pengaruh Kadar Gula Darah Terhadap Risiko Terjadinya Infeksi Saluran Kemih Pada Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Kediri - Putri, Lilia Danina; Diarti, maruni Wiwin; Pauzi, Iswari Wiwin; Tatontos, Erin Yustin (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background : Hyperglycemia creates a urinary environment conducive to bacterial growth, especially when accompanied by decreased immune function and impaired bladder emptying. The presence of glucose in the urine (glucosuria) promotes bacterial proliferation, increasing the risk of urinary tract infections (UTIs). Although diabetes mellitus (DM) cases are relatively high at Kediri Public Health Center, research examining the relationship between blood glucose levels and UTI risk remains limited. Therefore, it is important to assess whether elevated blood glucose levels influence the risk of UTIs in DM patients. Objective: To determine the effect of blood glucose levels on the risk of urinary tract infections in diabetic patients. Method: This study employed an analytical observational design with a cross-sectional approach. A total of 30 diabetic patients with blood glucose levels >200 mg/dL were selected as respondents. Their urine samples, which met the inclusion and exclusion criteria, were examined using purposive sampling technique. Urine analysis was conducted using the urine sediment method to detect the presence of bacteria as an indicator of urinary tract infection (UTI). The data were analyzed using the Chi-Square test. Result: Out of 30 respondents, 23 respondents tested positive for urinary tract infection (UTI) based on bacterial findings in the urine sediment. The Chi-Square test results showed a p-value of 0.002 (p < 0.05), indicating a statistically significant relationship between blood glucose levels and the incidence of UTI. Conclusion: Blood glucose levels have an effect on the incidence of urinary tract infections (UTIs) in diabetic patients.